Willingness to join community-based health insurance among rural households of Debub Bench District, Bench Maji Zone, Southwest Ethiopia - Haile, Melaku (BioMed Central, 2014)
BACKGROUND: Even though Ethiopia bears high burden of diseases, utilization of modern health care services is limited. One of the reasons for low utilization of healthcare services is the user-fee charges. Moving away from out-of-pocket charges for healthcare at the time of use is an important step towards averting the financial hardship associated with paying for health service. Prepaid plans for health are not accustomed in Ethiopia. Therefore, social and community based health insurance schemes were introduced since 2010. In this study, willingness of rural households in Debub Bench District, to join community based health insurance was assessed. METHOD: Cross-sectional community based study was conducted in Debub Bench District in March 2013 using a pretested structured questionnaire. Two stage sampling technique was used to select 845 households as study units which were allocated to the kebeles proportionately. The sampled households were selected using simple random sampling technique. Data were entered into EPIDATA 3.0 and analyzed with SPSS version 20. RESULT: Among 845 sampled households, 808 were interviewed (95.6% response rate). About 78% of the respondents were willing to join the scheme. Most of demographic, socioeconomic variables and social capital were found to be significantly associated with willingness to join community based health insurance. CONCLUSION: If the scheme is initiated in the district, majority of the households will enroll in the community based health insurance. Farmers, the married households, Bench ethnic groups and illiterate, the dominant segments of the population, are more likely to enroll the schemes. Therefore initiation of the scheme is beneficial in the district.